PENGELOLAAN DAN KONTRIBUSI HHBK KEMIRI TERHADAP PENDAPATAN MASYARAKAT DI KPHL SELAYAR - Makkarennu, Makkarennu; Alam, Syamsu; Pratiwi, Rini (PERENNIAL, 2022)
Non-Timber Forest Products (NTFPs) have a very important role for the community, especially the community around the forest. The community in Bontosikuyu District in the HPT KPHL Selayar area utilizes NTFPs in the form of candlenut. This study aims to describe the management of candlenut and calculate the contribution of the candlenut business to other farm incomes in the Bontosikuyu sub-district in the HPT KPHL Selayar area. This research was conducted from December 2021 to January 2022. The data collected in the form of primary data and secondary data. The results showed that the management of candlenut in Bontosikuyu District in the HPT KPHL Selayar area is still managed traditionally. People use candlenut business as a side business to increase income. The contribution given by the candlenut business to farmers' income is 75% or Rp. 122.860,000 per year.